2018
DOI: 10.3390/ijerph15112334
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Cadmium and Lead from Contaminated Soils Using Sophorolipids from Fermentation Culture of Starmerella bombicola CGMCC 1576 Fermentation

Abstract: Soil contaminated with Cd and Pb has caused sharp decrease of cultivatable soil and has been attracting increasing attention. Biosurfactants are efficient in solving the problem. However, little information is available about the influence of sophorolipids (SLs) on the remediation of Cd- or Pb-contaminated soil. The sophorolipids produced by Starmerella bombicola CGMCC 1576 were used to study the effects of Cd and Pb removal in batch soil washing from artificially contaminated soil. The removal efficiency of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…Furthermore, the high rate of metal removal as observed in this study have shown that surfactants could remove metals by ion exchange precipitation, dissolution and counterion association with the crude sugar surfactant, depicting superior performance similar to previous reports (Mulligan et al, 1999, 2004and Qi et al, 2018. Generally, the concentration of biosurfactant have been observed to be a critical factor in uencing heavy metal removal e ciency in this study and elsewhere (Mulligan et al, 2001 andQi et al, 2018). E ciencies of biosurfactant and soil washing agents in heavy metal removal Mulligan et al, (1999) showed the feasibility of removing cadmium, lead, and zinc with 2% anionic biosurfactants surfactin from soil that is low in exchangeable metal fractions.…”
Section: Heavy Metal Removal From Spiked Soil Using Crude Biosurfactantsupporting
confidence: 89%
“…Furthermore, the high rate of metal removal as observed in this study have shown that surfactants could remove metals by ion exchange precipitation, dissolution and counterion association with the crude sugar surfactant, depicting superior performance similar to previous reports (Mulligan et al, 1999, 2004and Qi et al, 2018. Generally, the concentration of biosurfactant have been observed to be a critical factor in uencing heavy metal removal e ciency in this study and elsewhere (Mulligan et al, 2001 andQi et al, 2018). E ciencies of biosurfactant and soil washing agents in heavy metal removal Mulligan et al, (1999) showed the feasibility of removing cadmium, lead, and zinc with 2% anionic biosurfactants surfactin from soil that is low in exchangeable metal fractions.…”
Section: Heavy Metal Removal From Spiked Soil Using Crude Biosurfactantsupporting
confidence: 89%
“…Pb has been listed as a hazardous heavy metal pollutant due to its high toxicity [72]. Long-term exposure to low concentrations of Pb leads to high toxic levels.…”
Section: Effect Of Lead Toxicity On Agricultural Soilmentioning
confidence: 99%
“…The rhamnolipid-aided washing method was proven by Nielson et al [152] to be more efficient than a synthetic surfactant (carboxymethyl-β-cyclodextrin). A sophorolipid-enhanced soil washing method was used to remove 83.6% of Cd and 44.5% of Pb by Qi et al [153]. However, in the presence of sophorolipid-producing Starmerella bombicolla , the removal increased to 95% of Cd and 52% of Pb.…”
Section: Biosurfactants For Environmental Remediationmentioning
confidence: 99%